Determinación de parámetros físico químico en cuatro materiales genéticos de chocho (Lupinus mutabilis) En cinco índices de cosecha. - Tituaña Arguero, Oscar David (2021)
This research was carried out at the Santa Catalina Experimental Station (INIAP) in the Department of Nutrition and Quality. The research work is focused on determining the physical-chemical properties of four genetic materials of lupine (lupinus mutabilis), 2 local varieties and 2 promising lines, where two factors were evaluated, which are: four genetic materials (INIAP 450 Andino, INIAP 451 Guaranguito , Native local ecotype and Peruvian local ecotype) and five harvest indices (Green, Lima, Yellow Lima, Yellow and Black). For the functional analysis, the ADEVA and Tukey's test (p <0.05) were calculated. Its composition was determined by carrying out proximal analyzes on both pods and grain, yielding the following results in pods with an average pH of 5.31 in the first index (green) and in the fifth index (black) with 5.98, in grain with an average pH of 5.59 in the first index (green) and in the fifth index (black) with 5.48 holding an acid pH, apparently there is not much difference. The identification of these properties allows to recognize the high nutritional value for its future use in the field of food and industry.